Exploring a Home Bias-Free Area on the Expected Return Frontier - Waluyo, Dwi Eko; Astuti, Sih Darmi; Prayitno, Agus; Ramasamy, Suganthi (Business Management Analysis Journal (BMAJ), 2024)
The aim of this research is to evaluate the efficient frontier of the Expected Value (EV) model for the top five stocks on the Malaysian and Indonesian stock markets. The study will explain that the identified home bias-free area can be better understood through the efficient frontier of a combined portfolio of stocks from both markets. The method involves comparing the efficient frontier graphs of the EV model, calculated using linear programming concepts with the SOLVER add-in. It was found that the optimal expected return on the Indonesian market yields better results with lower relative risk for each level of return achieved. The efficient frontier of the combined stocks from both countries also provides a better explanation of how to avoid home bias, as indicated by the identified home bias-free area. The portfolio results from combining stocks yield higher returns compared to the portfolios from each individual market and also exhibit a better coefficient of variation.To make the research findings more comprehensive, future studies could utilize broader return windows, such as weekly or monthly.